It's OK to Need a Friend - Quarto Publishing plc; AnneliesDraws (London : Wide Eyed Editions, 2021)
Friendship is one of life's greatest gifts - and one of its most important skills! As Little Brown Bear knows, having a friend to rely on makes all the difference in the world. But in order to have good friends, it's important to be a good friend. Part of the Little Brown Bear series, this book covers universal lessons on empathy, kindness and emotional intelligence needed to forge good friendships. See how Little Brown Bear pays attention to how his friends are feeling and thinks about how he can make them feel better.
Keywords: Bears -- Juvenile fiction; Friendship -- Juvenile fiction; Picture books